THE STIGMATIZATION OF THE MENTALLY ILL IN THE MEDIA: A STUDY FOR 2014-2018 WAS - Israelyan, T.V. (Modern Psychology, 2019)
The article is devoted to the problem of stigmatization of the mentally ill through the information provided by the media. The analysis of 1557 sources in the Federal media for the period from 2014-2018. The method of thematic content analysis was used to determine the nature and dynamics of publications for the period. That will allow to approach the issue of coverage of the problem of mental illness in the media more ethically and will lead to a policy of destigmatization of this category of citizens. This article will be useful for application in various fields: psychology, journalism, social work.
Keywords: media; mental illness; stigmatizing; words - stigma